The EFFECTIVENESS OF ADDING CORE STABILITY EXERCISE TO MICROWAVE DIATHERMY, ULTRASOUND AND MASSAGE INTERVENTION IN IMPROVING FUNCTIONAL ABILITY IN PATIENTS WITH OSTEOARTHRITIS GENU - Made Widnyana; I Putu Yudi Pramana Putra; I Made Niko Winaya; Anak Agung Gede Eka Septian Utama; I Dewa Gede Alit Kamayoga (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2023)
Osteoarthritis (OA) genu is a degenerative musculoskeletal system disorder in the knee joint which is characterized by slow and progressive loss of joint cartilage. OA genu causes disability and decreased functional abilities. The purpose of this study was to determine the effectiveness of adding core stability exercise to microwave diathermy, ultrasound and massage interventions in improving functional abilities in patients with OA genu. The research method used was an experimental pre-test and post-test control group design. There are two groups selected randomly with the block permutation technique. The treatment group consisted of 18 samples receiving core stability exercise, microwave diathermy, ultrasound and massage. The control group, totaling 18 samples, received microwave diathermy, ultrasound and massage. Functional ability was measured by the WOMAC questionnaire (Western Ontario and McMaster Universities Osteoarthritis Index). The research was conducted at a private physiotherapy clinic in Denpasar. The results of the study after the Paired T-Test was carried out in each group with a p value <0.05, this indicated that there was a significant difference between the results of the pre-test and post-test in each group. The different test between groups was carried out by the Independent Sample T-Test, obtaining a p value <0.05, this indicates that there is a significant difference between the treatment group and the control group. The conclusion of this study is that the addition of core stability exercise to microwave diathermy, ultrasound and massage interventions further enhances functional activity in OA genu patients. The implications of theoretical and practical research as additional knowledge and guidelines in providing effective interventions for OA genu conditions.